Prisons in the Late Ottoman Empire Microcosms of Modernity - Schull, Kent F. (Edinburgh University Press, 2014)
Contrary to the stereotypical images of torture, narcotics and brutal sexual behaviour traditionally associated with Ottoman (or 'Turkish') prisons, Kent F. Schull argues that these places were sites of immense reform and contestation during the 19th century. He shows that they were key components for Ottoman nation-state construction and acted as 'microcosms of modernity' for broader imperial transformation. It was within the walls of these prisons that many of the pressing questions of Ottoman modernity were worked out, such as administrative centralisation, the rationalisation of Islamic criminal law and punishment, issues of gender and childhood, prisoner rehabilitation, bureaucratic professionalisation, identity and social engineering. Juxtaposing state-mandated reform with the reality of prison life, the author investigates how these reforms affected the lives of local prison officials and inmates.